1997
DOI: 10.3109/10408449709089894
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Chronic Toxicity, Carcinogenicity, and Possible Mechanisms of Action of Inorganic Acid Mists in Animals

Abstract: Occupational exposure to inorganic acid mists containing sulfuric acid has been associated with increased laryngeal cancer. The primary objective of this review was to compile the literature regarding chronic toxicity and carcinogenicity of inorganic acid mists in laboratory animals. Several chronic toxicity studies had exposures of 1 year or longer. Whereas numbers of animals were limited, no evidence of neoplastic or preneoplastic lesions was reported. Two studies evaluated the carcinogenicity of inorganic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Sulfuric acid seems to be a relevant compound for human health effects in volatile nanoparticles. Inhalation of acid aerosols in laboratory animal studies causes genotoxic damage in cells (Soskolne et al, 1984;Swenberg and Beauchamp, 1997). Kilgour et al (2002) showed cell proliferation of the respiratory tract in rats due to exposure to sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfuric acid seems to be a relevant compound for human health effects in volatile nanoparticles. Inhalation of acid aerosols in laboratory animal studies causes genotoxic damage in cells (Soskolne et al, 1984;Swenberg and Beauchamp, 1997). Kilgour et al (2002) showed cell proliferation of the respiratory tract in rats due to exposure to sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Others have concluded that there is insufficient evidence to show a causal relationship between exposure to sulphuric acid mist and an excess of laryngeal cancer. It has been hypothesized that reduced pH resulting from exposure to acid mists may represent or contribute to any potential mechanism for cancer induction because it is known that acid pH causes genotoxic damage in cells and can affect also the toxicity of a number of chemicals (Soskolne et al, 1984;Swenberg and Beauchamp, 1997). There is limited information of relevance in earlier inhalation studies in experimental animals to support the hypothesis that sulphuric acid might be carcinogenic.…”
Section: Introductionmentioning
confidence: 80%
“…Although the short-term effects of sulphuric acid may either subside or progress, depending on a number of exposure-and duration-related factors, there are no adequate long-term studies investigating either the carcinogenicity of acid mists or potential mechanisms to help evaluate the biological plausibility of the association between respiratory tract cancer and occupational exposure to acid mists that forms the basis of the IARC classification (Swenberg and Beauchamp, 1997). In view of the limitations of the currently available experimental data to address the latter relationship, the study described here was designed to investigate the early response of the rat respiratory tract following exposure for either 5 or 28 days to sulphuric acid aerosols at target concentrations of 0.2, 1 and 5 mg m −3 and mass median aerodynamic diameters of 1 µm.…”
Section: Introductionmentioning
confidence: 99%
“…12 An association between occupational exposure to strong inorganic acid mists containing sulfuric acid and the risk increase of laryngeal cancer was seen. However, in many studies exposure to other carcinogens, such as asbestos, nickel, radon progeny and smoking, had not been taken into account.…”
Section: Discussionmentioning
confidence: 97%
“…11 However, the evidence from experimental animals regarding the carcinogenicity of inorganic acid mists is not conclusive. 12 Sulfuric acid is an abundant ambient air pollutant derived from manufacturing processes and from atmospheric oxidation of SO 2 , which is a primary effluent of fossil fuel combustion. In addition, sulfur trioxide gas hydrolyzes in the air or in mucous membranes to sulfuric acid.…”
mentioning
confidence: 99%